B-vitamins intake, DNA-methylation of One Carbon Metabolism and homocysteine pathway genes and myocardial infarction risk: The EPICOR study - Fiorito, G.; Guarrera, S.; Valle, C.; Ricceri, F.; Russo, A.; Grioni, S.; Mattiello, A.; Di Gaetano, C.; Rosa, F.; Modica, F.; Iacoviello, L.; Frasca, G.; et al. (Nutrition, metabolism, and cardiovascular diseases, 2014)
Several epidemiological studies highlighted the association between folate and B-vitamins low intake and cardiovascular diseases (CVD) risk. Contrasting results were reported on the relationship between folate intake and DNA-methylation. Folate and B-vitamins may modulate DNA-methylation of specific enzymes which are included in the One-Carbon Metabolism (OCM) and in the homocysteine (Hcy) pathways. The aim of the study was to evaluate whether DNA-methylation profiles of OCM and Hcy genes could modulate the myocardial infarction (MI) risk conferred by a low B-vitamins intake. Study sample (206 MI cases and 206 matched controls) is a case-control study nested in the prospective EPIC cohort. Methylation levels of 33 candidate genes where extracted by the whole epigenome analysis (Illumina-HumanMethylation450K-BeadChip). We identified three differentially methylated regions in males (TCN2 promoter, CBS 5′UTR, AMT gene-body) and two in females (PON1 gene-body, CBS 5′UTR), each of them characterized by an increased methylation in cases. Functional in silico analysis suggested a decreased expression in cases. A Recursively Partitioned Mixture Model cluster algorithm identified distinct methylation profiles associated to different MI risk: high-risk vs. low-risk methylation profile groups, OR = 3.49, p = 1.87 × 10−4 and OR = 3.94, p = 0.0317 in males and females respectively (multivariate logistic regression adjusted for classical CVD risk factors). Moreover, a general inverse relationship between B-vitamins intake and DNA-methylation of the candidate genes was observed. Our findings support the hypothesis that DNA-methylation patterns in specific regions of OCM and Hcy pathways genes may modulate the CVD risk conferred by folate and B-vitamins low intake.